HUBUNGAN TINGKAT PENDIDIKAN DAN TINGKAT PENGETAHUAN TENTANG KESEHATAN JIWA DENGAN SIKAP MASYARAKAT TERHADAP PASIEN GANGGUAN JIWA DI RW XX DESA DUWET KIDUL, BATURETNO, WONOGIRI - Tunjung Sri Yulianti; Wulan Meilina Putri Wijayanti (KOSALA : Jurnal Ilmu Kesehatan, 2016)
Introduction: management of mental health problems require complex handling.This of course must involve all parties. Mental patients who have recovered willbe returned to the family and society. This requires the readiness of families andcommunities. During this time in the community or family is still found theresponse and understanding is not correct to mental patients, but their role iscrucial to the recovery of patients with mental disorders.Purpose of the study: To determine the relationship between the level ofeducation and level of knowledge about mental health and community attitudestowards mental patients in RW XX Duwet Kidul Baturetno, Wonogiri .Subjects: were people in RW XX Duwet Kidul, Baturetno, Wonogiri aged adults(18-60 years ) some 108 people taken at random by the table KrecjieThis research method is correlation study involving the three variables, the firstvariable is the level of education, the second variable is the level of knowledgeand the third variable is the attitude of society, with logistic regression statisticaltest.Results: of the study obtained Nagelkerke R Square value of 0.279.Conclusion The study each variable is jointly influence public attitudes againstmental patients was 27.9%, while the remaining 72.1% is influenced by othervariables attitude.Keywords: Education Level, Level of Knowledge, Attitudes Society